Veterinary immunology : - Tizard, Ian R. (Saunders, 2000)
Veterinary Immunology: An Introduction has been the veterinary student's book of choice since 1977. The 7th edition continues this tradition and has the added benefit of full-color photos and important new information. Still an excellent first-level textbook for students of veterinary and comparative medicine, this text also assists veterinarians by informing them about recent developments in immunology as they relate to domestic animals